The Pedagogical Boxes’ Educational Program at the Homem do Nordeste Museum (Cadernos de Sociomuseologia, 2021)
In the administrative archive of the Joaquim Nabuco Foundation, we find the administrative documentation of the Museu do Homem do Nordeste (Muhne) since its foundation in 1979. By exploring this documentation, it was possible to observe the set of education initiatives in museums developed by the Muhne team in the 1990s. We found copies of the plans and reports of the educational program called "Didactic Boxes" dating from 1996 and 1997. Consulting the project, the activity report, the printed material containing instructions for using the didactic boxes and the disclosure pamphlet and the photos of the activities we understand the characteristics of the activity. The analysis of this specific action allowed us to perceive the set of epistemological principles that guided the museum team in their educational actions in the 1990s.Keywords: Didactic Boxes. Educational Program. Museum of the Northeast. Joaquim Nabuco Foundation.